NARRATIVE REVIEW: UTILIZATION OF HORTICULTURAL COMMODITY PLANT TISSUE CULTURE TECHNOLOGY AS A HALAL BIOTECHNOLOGY METHOD FOR FOOD AND PHARMACEUTICAL PURPOSES - M. Fariz Fadillah; Firman Rezaldi; Endang Safitri; Heny Sasmita; Ucu Wandi Somantri (Universitas Mathla’ul Anwar Banten, 2022)
Horticultural Commodity Plants are crop commodities consisting of vegetables, fruits, medicines, and spices. The advantages and disadvantages of horticultural commodity crops are one of the challenges that need to be considered in meeting the needs of the food and pharmaceutical industries which are increasingly out of control in terms of demand. One solution that can be given to researchers in the field of biotechnology in helping farmers to accelerate the process of plant propagation is through tissue culture techniques. The advantage of this method is that the plants produced are genetically the same and in harmony with their parents. The research method used is to collect data sources from the results of previous studies. The results of the review obtained that horticultural commodity plants propagated through tissue culture methods have prospects in the food and pharmaceutical fields. The conclusion in this review is that the tissue culture technique of horticultural commodity plants is a halal biotechnology method in vitro plant propagation to meet the interests of the food industry such as nutrition or nutriceuticals and pharmaceuticals such as cosmetics, herbal medicines, and phytopharmaceuticals. Several horticultural commodity plants with various problems through tissue culture techniques include vanilla, pepper, and tobacco. Purwoceng (Pimpinella pruatjan). Temu the princess (Curcuma petiolata). Puar (Elettaria sumatrana). Pulepandak (Rauwolfia serpentina). Pulai (Alstonia scholaris). Bidara upas (Merremia mammosa). Inggu (Ruta angustifolia). This is an example of a part of a horticultural commodity plant that has been successfully stored through tissue culture techniques as an in vitro germplasm collection.